The Influence of YouTube Content on Sexuality Education Toward Critical Thinking Ability of Children Aged 5–6 Years - Maghfiroh, Wus'atul; Fitri, Ruqoyyah; Fairuzillah, Muhammad Naufal; Widayati, Sri (Fakultas Keguruan dan Ilmu Pendidikan, 2025)
This research aims to analyze the influence of YouTube content on sexuality education toward the critical thinking ability of children aged 5–6 years at TK Aisyiyah Bustanul Athfal 14 Surabaya. The research employed a quantitative approach with a quasi-experimental nonequivalent control group design. The subjects consisted of 30 children divided into two groups, experimental and control, each comprising 15 children. The experimental group took a pre-test, received treatment in the form of sexuality education videos for five sessions, and then a post-test. The control group only took the pre-test and post-test without treatment. Data were collected through observation using a critical thinking rubric validated by experts, and analyzed using an independent t-test. The results showed a significant difference between the two groups. The mean score of the experimental group increased from 50.63 to 83.33, while the control group experienced only minimal improvement. The significance value of 0.000 (<0.05) proves that educational YouTube media influences the improvement of early childhood critical thinking ability.